Validity of the Microsoft Kinect™ in assessing spatiotemporal and lower extremity kinematics during stair ascent and descent in healthy young individuals. (October 2018) - Oh, Jeonghoon; Kuenze, Christopher; Jacopetti, Marco; Signorile, Joseph F.; Eltoukhy, Moataz
Highlights: The Kinect ™ provides valid and reliable hip and knee kinematics in stair negotiation. The Kinect ™ also provides valid and reliable hip and knee spatiotemporal data. Ease of testing, cost and space requisites make the Kinect ™ feasible for clinical use. Further research is required to improve assessment for the ankle. Abstract: Stair negotiation is one of the most challenging, yet frequently encountered, locomotor tasks in daily life. This study is the first attempt to investigate the capacity of the Kinect ™ sensor to assess stair negotiation spatiotemporal and sagittal plane kinematic variables. The goal of this study was to examine the validity of the Kinect ™ v2 sensor in assessing lower extremity kinematics and spatiotemporal parameters in healthy young individuals; and to demonstrate its potential as a low-cost stair gait analysis tool. Twelve healthy participants ascended and descended a 3-step custom-built staircase at their preferred speed, as spatiotemporal parameters and kinematics were extracted simultaneously using the Kinect ™ and a three-dimensional motion analysis. Spatiotemporal measures included gait speed, swing phase time, and double stance time. Kinematic outcomes included hip, knee, and ankle joint angles in the sagittal plane. Consistency (ICC2, 1 ) and absolute agreement (ICC3, 1 ) between the two systems were assessed using separate interclass correlations coefficients. In addition, ensemble curves and associated 90% confidence intervals (CI90) were generated for the hip, knee, and ankle kinematics to enable between system comparisons throughout the gait cycle. Results showed that the Kinect ™ has the potential to be an effective clinical assessment device for sagittal plane hip and knee joint kinematics and for some spatiotemporal parameters during the stair gait negotiation.